Distributional and Behavioural Effects of Child Care Subsidies - Thor Olav Thoresen (Statistics Norway, Research Department, 1995)
A methodology to describe the distributional and behavioural effects of child care subsidies is presented within a micro simulation framework. We discuss the effects of changing the governmental policy to support families with preschool children, from today's subsidisation of spaces at child care centres to an equal cash transfer to all families with preschoolers. In the decision model applied (Michalopoulos et al. 1992) the mother chooses consumption, market time and average quality of child care. The model is adjusted to the Norwegian child care market and data for mothers who both are employed and receiving child care subsidies (1990) are used, since this group of mothers is assumed to respond most to the reform. Weaknesses in data and simplifying model assumptions imply that the results must be used with caution. Results from our simulation experiment do not indicate any large decrease in mothers labour supply, when altering the transfer system. The reform will give a substantial decrease in inequality among households with preschoolers, since the child care subsidies very much favour well-off households.
Keywords: C81; D31; D63; H23; J13; J22; 330; Child care; distribution; household behaviour; inequality; labour supply; micro simulation; subsidies.